Recent Advances in Growth and Modification of Graphene‐Based Energy Materials: From Chemical Vapor Deposition to Reduction of Graphene Oxide. Issue 7 (9th April 2019) - Cai, Le; Yu, Gui
Abstract: Graphene is recognized as the next generation of energy materials due to its spectacular physical properties. Meanwhile, there are diverse synthetic methods toward graphene, and these methods have unique advantages to impel graphene to be suitable for different energy devices. Chemical vapor deposition and reduction of graphene oxide are classical methods for preparing graphene with various lattice structures and layer numbers, resulting in the tunability of graphene properties, whereby the synthetic methods have significant effects on energy device performances. Therefore, this review pays close attention to the discrepancies of graphene‐based materials prepared by these two methods for use in solar cells, rechargeable batteries, and electrocatalysis for hydrogen evolution. Furthermore, the modifications of graphene are introduced to offset the weaknesses of synthetic methods. Then, the review introduces graphene‐based flexible energy devices because graphene prepared by these two methods shows similarity in their mechanical stability. Finally, other synthetic methods are shortly highlighted to explain the importance of these two methods. The analyses for the discrepancies and similarity of graphene‐based materials in classical energy devices from the aspect of synthesis are beneficial to guide the preparation and modifications of graphene for maximizing its application and promote practical usage in the future. Abstract : Recent progresses in growth and modification of graphene‐based energy materials obtained by chemical vapor deposition and reduction of graphene oxide methods are comprehensively presented. The compatibility of graphene with a flexible power source is further reviewed. Studies on synthesis and engineering of graphene have great influences in graphene‐based energy devices and other applications.